2002
DOI: 10.1007/bf02818693
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of berberine—a constituent ofMahonia aquifolium

Abstract: The antimicrobial activity of the protoberberine alkaloid, berberine, isolated from Mahonia aquifolium, was evaluated against 17 microorganisms including two Gram-negative bacteria--Pseudomonas aeruginosa and Escherichia coli (both resistant and sensitive), two Gram-positive bacteria--Bacillus subtilis and Staphylococcus aureus, Zoogloea ramigera, six filamentous fungi--Penicilium chrysogenum, Aspergillus niger, Aureobasidium pullulans (black and white strain), Trichoderma viride (original green strain and bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(48 citation statements)
references
References 19 publications
2
45
1
Order By: Relevance
“…Berberine served as a positive control and demonstrated activity consistent with previous reports (Amin et al, 1969; Čerňáková and Košt’álová, 2002). …”
Section: Figuresupporting
confidence: 84%
See 1 more Smart Citation
“…Berberine served as a positive control and demonstrated activity consistent with previous reports (Amin et al, 1969; Čerňáková and Košt’álová, 2002). …”
Section: Figuresupporting
confidence: 84%
“… a MIC is defined as the concentration that caused OD 600 to be reduced by ≥ 95%. b Concentration is expressed as μg/mL of dried plant extract per mL of assay well volume. c Berberine served as a positive control and demonstrated activity consistent with previous reports (Amin et al, 1969; Čerňáková and Košt’álová, 2002). …”
Section: Figuresupporting
confidence: 80%
“…In addition, BBR has potential pharmacological effects, including effects on metabolic abnormalities, and antiarrhythmic, antihypertensive, anticancer, antidiabetic, and antihyperlipidenmic effects [23,24,25,26]. Accumulated evidence has shown that BBR can reduce lipogenesis in vitro and in vivo through a series of mechanisms, including the downregulation of the expression of peroxisome proliferator activated receptor γ (PPARγ) [27].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the recent studies indicate that berberine has various pharmacological effects including inhibition of intestinal fluid accumulation and ion secretion [129], anti-inflammatory [130], antimicrobial [131], anti-inhibition of smooth muscle contraction [132], and action on TJs [124] each of which may contribute to the antidiarrhea effect. The therapeutic dosage for most clinical usage is 200 mg orally two to four times daily [133].…”
Section: Berberinementioning
confidence: 99%